The Twelfth Annual Vancouver Folk Music Festival - Vancouver Folk Music Festival Societyet al (1989)
Jericho Beach Park THE TWELFTH ANNUAL VANCOUVER FOLK MUSIC FESTIVAL/ JULY 14, 15, 16, 1989 JERICHO BEACH PARK/ With over 200 performers from 18 countries Lillian Allen and the Revolutionary Tea Party Band - Ontario Frankie Armstrong - England Attila the Stockbroker - England B - Cuadro - Nicaragua Roy Bailey - England Ashwin Batish - India/U.S.A. Pierre Bensusan - France Suzanne Bird - Manitoba Heather Bishop - Manitoba Bisserov Sisters - Bulgaria Eric Bogle with Andy McGoin and Brent Miller - Australia Bob Bossin - B.C. Kevin Carmody - Australia John Cephas and Phil Wiggins - Virginia Hazel Dickens with Dudley Connell, Tony Trischka and Barry Mitterhoff - Washington, D.C. The Dots - B.C. Teresa Doyle with Richard Chapman and Chris Crilly - P.E.I. Eyuphuru - Mozambique Tisa Farrel, Thando Hyman, and M.C. Motion with D.J. Power - Ontario Folk Artists of Shaanxi - People's Republic of China Roy Forbes - B.C. Vasilios Gaitanos - Greece/U.S.A. Lennie Gallant and Band - P.E.I. Adrian Goizueta y el Grupo Experimental - Costa Rica Rufus Guinchard and Jim Payne - Newfoundland Joe Hall - Ontario Marie-Lynn Hammond with Marilyn Lerner - Ontario Harbord Trio - Ontario Barbara Higbie - California Horseflies - Massachusetts Inuit Throat Singers - N.W.T. Kin Lalat - Guatemala John Koerner - Minnesota Kolinda - Hungary Mustafa al Kurd - Palestine Larrikins - Australia Larry Long - Minnesota Celso Machado - Brazil Magical Strings - Washington Loreena McKennitt - Ontario Sue Medley - B.C. Mae Moore - B.C. Orealis - Quebec Ornaments - Latvia/U.S.S.R. Oyster Band - England Pied Pumpkin - B.C. Red Clay Ramblers - North Carolina Leon Rosselson - England Terilyn Ryan - B.C. Pete Seeger - N.Y. Patrick Sky - North Carolina Judy Small - Australia Soul Vibes - Nicaragua Spirit of the West - B.C. Jody Stecher and Kate Brislin - California Sun Rhythm Section - Tennessee Mahinarangi Tocker - New Zealand Lucie Blue Tremblay - Quebec La Troupe de Danse Rada de Georges Rodriguez - Haiti/Quebec Weddings, Parties, Anything - Australia Jennifer West, Rob Menzies and Friends - B.C. Women In The Round with Ashley Cleveland, Karen Staley, Pam Tillis, Tricia Walker - Tennessee and more!/ 6 Daytime Stages Saturday and Sunday Little Folks Area with special children's programming and activities 3 Evening Concerts Friday, Saturday and Sunday 18 Food Booths as varied as the music/ Tickets available in Vancouver at the Vancouver Folk Music Festival, 3271 Main Street, Vancouver, B.C., V5V 3M6 (604) 879-2931 (Including mail and phone orders and information); Black Swan Records, 2936 W. 4th Avenue, (734-2828); Highlife Records, 1317 Commercial Drive, (251-6964); Zulu Records, 1869 W. 4th Avenue, (738-3232); and all Ticketmaster Outlets (280-4444). In Victoria at Mezzrow's, 3625 Douglas Street, (381-2633) and all Ticketmaster Outlets throughout the province./ The bird is the word/ Sponsored by the Vancouver Folk Music Festival Society with assistance from the Vancouver Board of Parks and Recreation; the City of Vancouver; the Province of British Columbia Ministry of Municipal Affairs, Recreation and Culture; Communications Canada; Touring Office of the Canada Council; Employment and Immigration Canada - under the Job Development Program; Canadian Broadcasting Corporation; and Vancouver Co-operative Radio 102.7 FM. Thanks Folks!/ Communications Canada/ The Canada Council Touring Office Conseil des Arts du Canada Office des tournees/ Design: Dugg Photo: Chris Cameron/ Cum Res Insolitae Fiunt, Profiteuntur Insoliti